Design Improvement and Cost Reduction of a Hair Dryer: A DFMA and Value Engineering Approach - Mak Zhen Wei,; Azli Nawawi, (Progress in Engineering Application and Technology, 2024)
This paper focuses on evaluating the performance of the original hair dryer in terms of cost and design efficiency and proposes modifications and improvements through integrated DFMA (Design for Manufacture and Assembly) and Value Engineering analyses. Grounded in the DFMA theory, the objective is to obtain the most cost-effective products and production methods while simplifying the manufacturing process. The optimization of the hair dryer's configuration aims to enhance speed and affordability in both construction and assembly. Through the elimination of certain components, the improved design not only reduces the difficulty of manufacturing but also lowers production costs. The methodology involves a comparative performance analysis between the original and improved designs, utilizing both DFMA and VE principles. Six significant improvements, informed by these methodologies, contribute to a 3% enhancement in design efficiency—from 59% to 62%. This enhanced design demonstrates notable progress in assembly efficiency, parts reduction, cost-effectiveness, and overall design efficiency. The findings provide valuable insights for the development of improved designs and cost-reduction strategies in the context of hair dryer manufacturing.